Engineered Ultrasmall Nanoparticle Drug‐Immune Conjugates with "Hit and Run" Tumor Delivery to Eradicate Gastric Cancer (Adv. Therap. 3/2023). Issue 3 (10th March 2023) - Zhang, Li; Aragon‐Sanabria, Virginia; Aditya, Anusha; Marelli, Marcello; Cao, Tianye; Chen, Feng; Yoo, Barney; Ma, Kai; Zhuang, Li; Cailleau, Thais; Masterson, Luke; Turker, Melik Z.; et al.
Abstract : Receptor‐mediated endocytosis of a precision engineered HER2‐targeting ultrasmall silica nanoparticle drug conjugate after binding the HER2 extracellular domain on gastric cancer cells. This is reported by Ulrich Wiesner, J. Anand Subramony, Michelle S. Bradbury, and co‐workers in article number 2200209 .